Testing the Effectiveness of Anti-Mosque Lotion from the Formulation of Male Breadfruit (Artocarpus altilis) and Lemon (Cymbopogon citratus) Flower Extract - Nurasia; Ilmiati Illing; Riska Nurhayati (BENCOOLEN JOURNAL OF PHARMACY, 2022)
This study aims to compare the concentration of extracts of male Breadfruit and Lemongrass stalks which are effective as mosquito repellent lotions. Male Breadfruit (Artocarpus altilis) and Lemongrass (Cymbopogon citratus) stems can be used as natural mosquito repellents because they contain active ingredients (compounds) that do not liked by mosquitoes. The research method used in this study includes sample preparation, maceration using 96% ethanol, the distillation process to separate the filtrate and residue, making lotion formulations using the oil phase and water phase with different sample concentrations, then carried out three stages of testing, namely organoleptic test. , pH test and effectiveness test to determine the effectiveness of the male flower repellent lotion of Breadfruit (Artocarpus altilis) and Lemongrass (Cymbopogon citratus) stems. The results obtained showed that the effective concentrations used as mosquito repellent lotions for male Breadfruit (Artocarpus altilis) and Serai (Cymbopogon citratus) flowers were 15 mL and 20 mL of male flower extract of Breadfruit and Serai stems.